Effects of resistance training on performance in competitive badminton players: a systematic review - Wang, T.; Guan, N. Y.; Amri, S.; Kamalden, T. F.; Gao, Z. (Frontiers in Physiology, 2025)
Background: Resistance training (RT) is critical in enhancing athletic performance by improving physical fitness and sport-specific skills. However, there is a lack of systematic evaluation regarding the effects of RT on competitive athletes. This systematic review aims to explore the evidence of the impact of RT on physical performance and badminton-specific skills among competitive badminton players, providing actionable insights for optimizing training.